3D Surfaces Reconstruction and Volume Changes in Underwater Environments Using MSIS Sonar - Justo, Bruno; Santos, Matheus; Drews, Paulo; Arigony, Jorge; Vieira, Antonio (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
3D Surfaces Reconstruction and Volume Changes in Underwater Environments Using MSIS Sonar